2016
DOI: 10.1074/jbc.m116.737569
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Differentiation-associated Gene 7/IL-24 Exerts Cytotoxic Effects by Altering the Alternative Splicing of Bcl-x Pre-mRNA via the SRC/PKCδ Signaling Axis

Abstract: A number of studies have demonstrated that the overexpression of Bcl-x(L) in cells confers apoptosis resistance as well as cooperates with oncogenic factors (e.g. c-Myc) in tumorigenesis (1-10). The regulation of Bcl-x(L) expression can be complex at times, consisting of both transcriptional and post-transcriptional processes. In regard to post-transcriptional processing/ alternative splicing, the BCL-x gene, via alternative 5Ј splice site (5ЈSS) 5 selection within exon 2, produces either the Bcl-x(s) isoform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…Cells were passaged once every 3 to 5 days (ϳ90% confluence), and all experiments were performed during the first 12 passages. Antibodies were purchased from Cell Signaling Technology with the exception of anti-CPEB2 (Santa Cruz Biotechnology) and anti-HIF1␣ (Abcam) (7,(23)(24)(25)(26)(27).…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cells were passaged once every 3 to 5 days (ϳ90% confluence), and all experiments were performed during the first 12 passages. Antibodies were purchased from Cell Signaling Technology with the exception of anti-CPEB2 (Santa Cruz Biotechnology) and anti-HIF1␣ (Abcam) (7,(23)(24)(25)(26)(27).…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%
“…Plasmid transfections were accomplished using the Effectene system (Qiagen) according to manufacturer's instructions as described previously (7,(22)(23)(24)(25)(26) or Amaxa Nucleofector (Kit V).…”
Section: Transfection (Plasmid)mentioning
confidence: 99%
See 2 more Smart Citations
“…IL-24 expression is lost in most cancer cells of human origin [2][3][4]. Studies have shown that loss of IL-24 expression is correlated with disease progression in prostate cancer [5], breast cancer [6], colon cancer [7], neuroblastoma [8], acute leukemia [9], oral squamous cell carcinoma [10,11], lung cancer [12] and other cancers [13][14][15][16][17]. Exogenous IL-24 expression has anti-tumor, anti-angiogenic and anti-metastatic properties and suppresses various signaling pathways, without harming normal cells [2][3][4][5].…”
mentioning
confidence: 99%